When China rules the world the rise of the Middle Kingdom and the end of the western world - Jacques, Martin (Allen Lane, an imprint of Penguin Books, 2009)
Explains how China's ascendance as an economic superpower will alter the cultural, political, social, and ethnic balance of global power in the twenty-first century, unseating the West and in the process creating a whole new world.